2015
DOI: 10.1021/acs.joc.5b01300
|View full text |Cite
|
Sign up to set email alerts
|

Directed Metalation–Suzuki–Miyaura Cross-Coupling Strategies: Regioselective Synthesis of Hydroxylated 1-Methyl-phenanthrenes

Abstract: A general, efficient, and regioselective synthesis of a series of hydroxylated 1-methylphenanthrenes 9 by a combined directed ortho metalation (DoM)-Suzuki-Miyaura cross-coupling-directed remote metalation (DreM) sequence is reported. Diversity to this methodology was achieved by a regioselective DoM rather than DreM reaction, affording more highly substituted phenanthrols ( Table 2 ). Application of the turbo-Grignard reagent (i-PrMgCl·LiCl) in the Ni-catalyzed Corriu-Kumada reaction gave efficient decarbamoy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 92 publications
(141 reference statements)
0
31
0
Order By: Relevance
“…The right protecting group can serve a double purpose as it can easily be cleaved from the phenanthrene to remove the oxygen left after the DreM reaction. Although the less expensive way of doing this is through a carbamate (25), the more commonly used triflate was used since the cleavage of carbamate inevitably produce a few percent of the alkylated byproduct that would be inseparable from the product by moderate resolution chromatography. The DreM reaction followed by protection with triflic anhydride using 2,6-lutidine as base gave triflates 3a-d in 67-75% yield.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The right protecting group can serve a double purpose as it can easily be cleaved from the phenanthrene to remove the oxygen left after the DreM reaction. Although the less expensive way of doing this is through a carbamate (25), the more commonly used triflate was used since the cleavage of carbamate inevitably produce a few percent of the alkylated byproduct that would be inseparable from the product by moderate resolution chromatography. The DreM reaction followed by protection with triflic anhydride using 2,6-lutidine as base gave triflates 3a-d in 67-75% yield.…”
Section: Resultsmentioning
confidence: 99%
“…Another main route to the simple substituted phenanthrenes is the combination of directed ortho metalation (DoM), Suzuki-Miyaura cross-coupling and directed remote metalation (DreM) to form phenanthrenes (23). This reaction sequence has been used successfully to make a wide range of substituted phenanthrenes (24,25). Herein, we present a scale-up of the Snieckus route (24) to 4b and 4c and utilize its flexibility to make 4a and 4d.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These tactics rely on strategically installed metal‐active groups and such starting materials require additional steps to prepare them from feedstock chemical sources. Moreover, harsh reaction conditions are generally needed, thus reducing their versatility and simplicity 10ad…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that conditions reported by Jørgensen and Snieckus may be favorable for couplings in the presence of methoxy groups. 88 They noted that when attempting Suzuki reactions on their desired systems with conditions similar to those described above involving Pd(PPh 3 ) 4 , success was limited. Upon exploration of additional conditions, they found that the use of Pd 2 (dba) 3 , SPhos, K 2 PO 4 , and toluene at reflux was more effective for obtaining their desired biaryl products.…”
mentioning
confidence: 99%